Development of the Ethnomathematics-Based Mathematics Teaching Materials to Improve Conceptual Understanding of Madrasah Ibtidaiyah Students in Lombok, Indonesia - Naili Lumaati Noor; Eva Luthfi Fakhru Ahsani; Awwalina Ainurrokhimah; Muhamad Miftah Farid (UIN Siber Syekh Nurjati Cirebon, 2024)
AbstractMathematics learning requires real situations that students often face. Using the context around students can make mathematics learning easy for students to understand. This research aims to develop ethnomathematics-based mathematics teaching materials to improve the conceptual understanding of Madrasah Ibtidaiyah/Islamic elementary school students in Lombok, Indonesia, that are feasible and practical. This research is research and development with the development of a 4D model consisting of defining, designing, developing, and disseminating. The resulting product is ethnomathematics-based mathematics teaching materials for grade IV students of Madrasah Ibtidaiyah in Lombok, Indonesia. The results of the development of teaching materials at the level of feasibility from the validation of material experts obtained a score of 39.5 with a feasible category, cultural experts obtained a score of 19.5 with a feasible category, and media experts obtained a score of 40.8 with a very feasible category. From the results of the product trial, it is known that the resulting product falls into the practical criteria, namely from student responses obtaining an assessment of 91% with a very positive category. The implications of the research are expected to increase the mathematical conceptual understanding of madrasah ibtidaiyah students to strengthen national cultural identity.Keywords: ethnomathematics, sasak culture, teaching materials, madrasah ibtidaiyah students.AbstrakPembelajaran matematika memerlukan situasi nyata yang sering dihadapi oleh siswa. Dengan menggunakan konteks yang ada di sekitar siswa, membuat pembelajaran matematika mudah dipahami oleh siswa. Penelitian ini bertujuan untuk mengembangkan bahan ajar matematika berbasis etnomatematika untuk meningkatkan pemahaman konsep siswa Madrasah Ibtidaiyah di Lombok, Indonesia yang layak dan praktis. Penelitian ini merupakan penelitian dan pengembangan dengan pengembangan model 4D, terdiri atas define (pendefinisian), design (perancangan), develop (pengembangan), dan disseminate (penyebaran). Produk yang dihasilkan adalah bahan ajar matematika berbasis etnomatematika untuk siswa kelas IV Madrasah Ibtidaiyah di Lombok, Indonesia. Hasil pengembangan bahan ajar pada tingkat kelayakan dari validasi ahli materi diperoleh skor 39,5 dengan kategori layak, dari ahli budaya diperoleh skor 19,5 dengan kategori layak, dan dari ahli media diperoleh skor 40,8 dengan kategori sangat layak. Dari hasil uji coba produk diketahui bahwa produk yang dihasilkan masuk dalam kriteria praktis, yaitu dari respon siswa memperoleh penilaian 91% dengan kategori sangat posititf. Implikasi penelitian ini diharapkan dapat meningkatkan pemahaman konsep matematika siswa madrasah ibtidaiyah, sehingga memperkuat jati diri budaya bangsa.Kata kunci: etnomatematika, budaya sasak, bahan ajar, siswa madrasah ibtidaiyah.